Kompleksitas Kelembagaan Negara Indonesia: Tinjauan Literatur Terhadap Struktur, Fungsi, Dan Koordinasi Organisasi Pemerintahan - Ardhy Asyhabie; Reinohaadi Reinohaadi; Hasdan Syaf Maulana; Jumiati Jumiati; Boni Saputra (CV. ITTC INDONESIA, 2025)
The state and government organizations in Indonesia have a complex structure in a presidential and decentralized system. This article aims to examine the institutional classification and relationships between institutional entities in this context. The method used is library observation of various academic sources and relevant official documents. The results of the study indicate a variety of patterns of authority arrangements and coordination mechanisms between the central and regional governments, including the roles of ministries, institutions, agencies (K/L/D/I) and state supporting bodies. Discussion of the importance of an in-depth understanding of the structure and relationships between state and government organizations as a basis for optimizing effective, accountable and coordinated governance. The conclusion of this article emphasizes that strengthening institutional coordination is key to improving the quality of governance in Indonesia.